Assessment of poor functional status and post-acute care needs following primary ovarian cancer debulking surgery. Issue 2 (6th January 2020) - Roy, Allison Grace; Brensinger, Colleen M; Latif, Nawar; Giuntoli, Robert; Kim, Sarah; Morgan, Mark; Ko, Emily M
Abstract : Introduction: Poor baseline functional status is associated with adverse surgical outcomes. Additionally, decline in the postoperative setting may result in the delay of additional treatments, impacting overall survival. This study assesses the incidence and risk factors for functional decline following primary ovarian cancer debulking surgery in previously independent women using discharge location as a surrogate. Methods: All patients with a postoperative diagnosis of ovarian cancer who underwent surgical debulking and had documentation of discharge location were identified using the 2011–2012 American College of Surgeons National Surgical Quality Improvement Program database. Patients were excluded if their baseline functional status was dependent or partially dependent, or if they died before discharge. Discharge destination was dichotomized as home versus non-home. Descriptive data included demographics, comorbidities, and perioperative outcomes. Multivariable logistic regression was used to evaluate the association of clinical and surgical factors on discharge destination. Results: 1786 patients met the criteria for analysis; 120 (6.7%) patients were discharged to non-home. Differences between home and non-home discharges included age (53.2% vs 83.3% ≥60), body mass index (26.5 vs 27.8 median), comorbidities (45.2% vs 64.2% with ≥1), and complications (8.6% vs 30.0% with ≥1, all p<0.05). In multivariable logistic regression analyses, only increasing age and complications were independently associated with discharge to non-home. Those age ≥70 had 9.0 times the risk (95% CI 3.5 to 23.4; p<0.001) as age <50. The presence of one or more postoperative complications carried 4.5 times (95% CI 2.9 to 7.0; p<0.001) the risk of those without complications. 30 day mortality was also increased in patients discharged to non-home. Discussion: 6.7% of previously independent ovarian cancer patients were discharged to non-home following surgery. Major risk factors for non-home include older age, comorbidities, and postoperative complications. Efforts to optimize baseline functional status and minimize surgical complications may improve discharge rates to non-home and postoperative functional status.